Estudio de Competitividad del Sector Hotelero de la Ciudad de Nueva Loja - Betancourt Perenguez, Jessica Patricia (2016)
For the preparation of the present paper is part from the identification of a problem that is around the possible lack of business competitiveness and marketing strategies determine the positioning against the competition, in order to recommend technical procedures that improve the profitability of hotels in the city and the services of Nueva Loja, in the canton of Lago Agrio, in the province of Sucumbios, problems arising with the bases of an initial survey conducted to the owners of these establishments of hotel and tourist service. The main objective of the research on the subject "study of competitiveness in the SECTOR of hospitality in the city of NUEVA LOJA" is to study the conditions of the existing competitiveness of the hotels in this sector on the basis of the same, and the Ecuador improve the economic and competitive development of the hotel company, building to the effect a minimum strategic plan if the owners decide to deploy it immediately. To learn more the problem, in this document it boasts an extensive review of literature in different texts, journals and reports of people specializing in competitive processes that are part of the globalization in order to learn basic concepts and necessary to carry out this project. Once understood the problem with the literature reviewed is determined the size of the population and their respective sample to be able to survey respondents of quality, in this case the owners of the properties in a group of fifteen business and likely users of the services in the amount of 383 surveys, the same as after applied and many contribuyeros factors tabulated determined 6 to build an array that contains the strengths and weaknesses settlements, seen from the insider's perspective. In order to meet the external forces that have influence on analyzed sector, an analysis of them from multiple edges, thus: economic, social, environmental factors among others. analysis that allowed to build influential elements from the point of view of opportunities and threats. In study is taken as the basis for the strategies proposed matrix SWOT, which was evaluated with the construction of another important support which is the matrix of evaluation of internal (EFI) factors and evaluation of external factors (EFE) matrix, to propose an array of solutions and to leave suggested major and immediate measures to increase the competitiveness of hotel business in the city of Nueva Loja. The main strategic elements from the point of view of the research carried out, have to do with aspects such as business philosophy, advertising, improving service, promotions, training and motivation for the staff. Five objectives arises from construction business philosophy for hotels, improvement and promotion of advertising and promotion, staff training and incentives to pay for the loyalty of users with tours of tourist routes and finally with a process of accounting and financial analysis e. Then proceeded to the conclusions from the information obtained during the development of the project, among which the most important is that e l hotel 7 sector in the city of Nueva Loja, currently has infrastructure, technology, personnel and competitive prices, but its positioning in the market is weak. An important recommendation is focused to ensure that this work is valued by the owners of the hotels so that it allows them to position the brand, leverage market opportunities especially as a place of tourist attraction and face competition.